(3aUhU GdMces - (3GHf YQHj, eMjj GdOjfs; (3Yajaj, CHh GdYdGs ((3GdbGgQIs (3CbdGe YQHjI ddfTQ hGdJhRjYs, 2023)
(3jYO cJGH (B"(3GdaUhU(B" (3CYXe eDdaGJ GHf YQHj cdgG bOQkG hCYebgG ZhQkG hCHYOgG CKQkG aj JTcjd GdYbjOI GdUhajI aj YUQg haj GdCLjGd GdJj JdJg, abO bQQ ePgH hMOI GdhLhO aj UhQJg GdfgGFjI hhVY dg eUWdMkG UhaqjG cGedkG GSJeOg ef cd eUOQ hSYg Cf jSJeO efg, cGdbQBf GdcQje hGdMOjK hYde GdcdGe hGdadSaI GdeTGFjI hGdadSajI GdCadGWhfjI GdMOjKI hGdZfhUjI GdeSjMjI, hGdQhGbjI hadSaI ajdhf GdjghOj, ceG GfJaY HeUWdMGJ GdESeGYjdjI GdHGWfjI hGdbQGeWI hENhGf GdUaG heJUhaI GdESdGe GdeJbOejf Ydjgs
Keywords: (3GdJUha GdESdGejs; (3GdWQb GdUhajIs